A systematic review of MAKO‐assisted unicompartmental knee arthroplasty. Issue 5 (14th June 2020) - Lin, Jiyan; Yan, Shigui; Ye, Zhaoming; Zhao, Xiang
Abstract: Unicompartmental knee arthroplasty (UKA), which has many potential advantages compared with total knee arthroplasty, was widely used across the world in recent years. The introduction of the robot systems greatly makes up for the defects of the conventional UKA surgery such as higher complication rates and revision rates. MAKO system, a new image‐guided robot system relies on a preoperative computed tomography scan to assist in preoperative mapping and planning, offers an opportunity to improve the outcome of UKA surgeries. In order to have a more comprehensive and in‐depth understanding of MAKO‐assisted UKA, the studies on MAKO‐assisted UKA were summarized. MAKO‐assisted UKA is better than conventional UKA surgery on implant accuracy, soft tissue balance, patient function scores and satisfaction, complications rates, and learning curve in short‐term outcome; however, the mid‐term and long‐term outcomes of MAKO‐assisted UKA need to be further studied.